Analisis Kebutuhan Pelatihan Standar Proses Berbasis Data Pemetaan Mutu Pendidikan Pada Jenjang Sekolah Dasar Di Kota Cirebon - Endang Yuda Nuryenda; Dapung Dapung (Universitas Negeri Makassar, 2021)
In order to improve the quality of education in accordance with the National Education Standards, it is necessary to conduct an in-depth study of the achievement of the process standards carried out in elementary schools in Cirebon City in order to obtain an accurate picture of the need for or lack of training in process standards. The purpose of this study was to obtain a description of the analysis of the requirements for the Standard Process training at the Elementary School in Cirebon City. The method used in this research is the quantitative descriptive analysis based on quality report cards in 2019. The results show that from 135 elementary schools in the city of Cirebon for school indicators planning the learning process according to the provisions with the average category of achievement towards SNP 4, for indicators the learning process is implemented with the average achievement category towards SNP 4, while for indicators of supervision and authentic assessment carried out in the learning process with an average category of achievement towards SNP 4. The conclusion of this study is that the fulfillment of educational process standards for Elementary Schools in Cirebon City is still is in the category towards SNP 4 so that it still requires an increase in the achievement of the National Education Standards through training.